2011
DOI: 10.1097/ana.0b013e31821bc003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Intraoperative MRI Guidance for Craniotomy and Tumor Resection in the Semisitting Position

Abstract: The iMRI-guided brain tumor resection is feasible in combination with semisitting patient positioning. However, special safety precautions must be followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Thus, incomplete resection of LGG and histopathological undergrading of gliomas is not uncommon in the routine neurosurgical practice (6)(7)(8)(9)(10)(11)(12)(13)(14). In the last decades, different techniques were introduced into the neurosurgical operating room for improved intraoperative visualization of LGG tissue such as neuronavigation with multimodal imaging data, intraoperative MRI and advanced ultrasound (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, incomplete resection of LGG and histopathological undergrading of gliomas is not uncommon in the routine neurosurgical practice (6)(7)(8)(9)(10)(11)(12)(13)(14). In the last decades, different techniques were introduced into the neurosurgical operating room for improved intraoperative visualization of LGG tissue such as neuronavigation with multimodal imaging data, intraoperative MRI and advanced ultrasound (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Các phương pháp khác (tia xạ, xạ phẫu, hóa chất, quang động học,...) chỉ có tác dụng hỗ trợ nhằm ngăn ngừa hoặc kéo dài thời gian u tái phát hoặc chỉ định khi phẫu thuật không lấy được triệt để khối u. Phẫu thuật (kể cả không lấy hết u) cũng làm tăng hiệu quả các phương pháp điều trị hỗ trợ như xạ trị, hóa trị, quang động học sau mổ. Kết quả mổ lấy u cho thấy đa số mổ lấy toàn bộ u thực hiện được cho 30 bệnh nhân (58,8%), mổ lấy gần hết u ở 18 bệnh nhân (35,3%), và lấy một phần u ở 03 bệnh nhân (5,9%), không bệnh nhân nào không lấy được u. Kết quả nghiên cứu này phù hợp với nghiên cứu của Stupp, tỉ lệ bệnh nhân được phẫu thuật viên ghi nhận lấy một phần u (lấy <50% thể tích u) là 61%, lấy phần lớn u (lấy >50% thể tích u) là 39% [6], nghiên cứu của Senft thì tỉ lệ bệnh nhân được lấy phần lớn u là 68% [7].…”
Section: Bàn Luậnunclassified
“…To overcome these shortcomings of preoperative imaging, intraoperative MRI has been introduced into the neurosurgical field. Many studies have reported that intraoperative MRI-guided surgery improves resection quality without increasing neurological complications and has a positive impact on survival [13][14][15]. In a randomized controlled trial, intraoperative MRI offered 96% total resection in comparison with 68% without it [13].…”
Section: Conventional Imaging-guided Surgerymentioning
confidence: 99%